MATHEMATICAL MODELING OF PASSENGER CORRESPONDENCE OF URBAN TRANSPORT SYSTEM - A. Sorokin (Вестник Северо-Кавказского федерального университета)
The article discusses the problems of improving the transport infrastructure and points out the possibility of using passenger correspondence matrices to model the urban transport network. Models of transport systems are considered. A review of software and mathematical tools for transport modeling is given. The scheme of modeling traffic flows is given. It is indicated that the dominant role in determining the load on the urban transport network is the construction of a correspondence matrix. A descriptive description of the purpose of correspondence matrices is given. Four classes of mathematical models are considered for calculating the elements of the correspondence matrix. The advantages and disadvantages of the models are investigated.